Influence of specimen size on the consolidation properties of soft Rangsit clay - Ismail, Muhammad Ali; Holmberg, Soren; Brenner, R.P.; Onodera, T. F.; Government of United States of America (Bangkok : Asian Institute of Technology, 1977)
This thesis presents the results from an investigation of the influence of specimen size on the measured consolidation properties of the Soft Rangsit Clay. It is generally assumed that small size specimens of inhomogeneous clay when tested in the laboratory do not yield results that are representative of the in-situ consolidation properties. The Soft Rangsit Clay deposit contains fissures and thin lenses of sand and silt, and is therefore considered an inhomogeneous clay. Six series of consolidation tests were carried out on specimens with diameter of 2.511 , 4" and 911 {u2022} Specimens were cut both horizontally and vertically they were tested in hydraulic oedometers with pore pressure measurements. For all practical purposes, the tests showed that the size of the specimen had no influence on the measured consolidation properties. Both horizontally and vertically cut specimens yielded a preconsolidation pressure which was of the same order of magnitude for both type of specimens.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1977
Keywords: Soil consolidation; Clay -- Testing